Agomelatine pretreatment prevents development of hyperglycemia and hypoinsulinemia in streptozotocin-induced diabetes in mice - Ozcan, Mete; Canpolat, Sinan; Bulmus, Ozgur; Ulker, Nazife; Tektemur, Ahmet; Tekin, Suat; Kelestimur, Haluk (Wiley, 2019)
The main objective of this study was to investigate potential effectiveness of agomelatine pretreatment in the prevention of diabetes itself and encephalopathy, with a focus on brain tissue oxidative stress and inflammatory processes in streptozotocin (STZ)-induced diabetic mice. Interleukine-1 beta (IL-1 beta) and TACR1 (NK1), which is a tachykinine receptor, were used for the investigation of inflammation in the brain regions including raphe nucleus, periaqueductal gyrus (PAG), amygdala, and nucleus accumbens. The effects of agomelatine on total antioxidant capacity were also evaluated. In the in vitro part of the study, the effects of agomelatine on cell viability were investigated in dorsal root ganglion (DRG) neurons. Fasting blood glucose levels were measured 72 h after STZ injection to determine the diabetic condition. Agomelatine pretreatment prevented both hyperglycemia and hypoinsulinemia in STZ-treated mice. When STZ was injected to induce diabetes in mice, neither hyperglycemia nor hypoinsulinemia was developed in agomelatine pretreated mice and 6 weeks after development of diabetes, agomelatine treatment significantly decreased levels of IL-1 beta mRNA in raphe nucleus and nucleus accumbens. TACR1 mRNA levels were lower in raphe nucleus, PAG, and amygdala of agomelatine-treated diabetic mice. The increase in total antioxidant capacity after agomelatine administration may responsible for its beneficial effect in the prevention of diabetes. We showed that agomelatine reversed high glucose-induced cell viability decreases in DRG neurons. Both the antihyperglycemic and antioxidant effects of agomelatine might have contributed to the DRG neuron viability improvement. In conclusion, agomelatine seems to both prevent development of diabetes and reverse the encephalopathic changes caused by diabetes.
Keywords: agomelatine; antioxidant capacity; cell viability; diabetes; melatonergic (MT1 and MT2) receptors; serotonergic (5-HT2C) receptor